Taking action through redesign: Norwegian EFL learners engaging in critical visual literacy practices. Issue 2 (3rd April 2022) - Brown, Cecilie Waallann
Abstract: This article presents results from a case study which investigated how Norwegian English foreign language (EFL) learners, roughly aged 16–17, take action through redesigning a multimodal advertisement. Data was collected from a redesign task at the end of a 16-week intervention, in which three classes were introduced to critical visual literacy practices as an integrated part of their EFL lessons. A thematic analysis of the learners' deconstructions, multimodal redesigns and written reflections showed that the learners engaged with one or more of the themes power, diversity, identification and symbolism during the task. Utilising a variety of semiotic resources, the learners were largely successful in identify underlying ideologies in the advertisement and addressing these in their redesigns, thus creating a new version of the world which was more in line with their personal beliefs.